Effect of Acupuncture vs Sham Acupuncture on Patients With Poststroke Motor Aphasia - Boxuan Li; Shizhe Deng; Bifang Zhuo; Bomo Sang; Junjie Chen; Menglong Zhang; Guang Tian; Lili Zhang; Yuzheng Du; Peng Zheng; Gonglei Yue; Zhihong Meng (2024)
Importance Motor aphasia is common among patients with stroke. Acupuncture is recommended as an alternative therapy for poststroke aphasia, but its efficacy remains uncertain. Objective To investigate the effects of acupuncture on language function, neurological function, and quality of life in patients with poststroke motor aphasia. Design, Setting, and Participants This multicenter, sham-controlled, randomized clinical trial was conducted in 3 tertiary hospitals in China from October 21, 2019, to November 13, 2021. Adult patients with poststroke motor aphasia were enrolled. Data analysis was performed from February to April 2023. Interventions Eligible participants were randomly allocated (1:1) to manual acupuncture (MA) or sham acupuncture (SA) groups. Both groups underwent language training and conventional treatments. Main Outcomes and Measures The primary outcomes were the aphasia quotient (AQ) of the Western Aphasia Battery (WAB) and scores on the Chinese Functional Communication Profile (CFCP) at 6 weeks. Secondary outcomes included WAB subitems, Boston Diagnostic Aphasia Examination, National Institutes of Health Stroke Scale, Stroke-Specific Quality of Life Scale, Stroke and Aphasia Quality of Life Scale–39, and Health Scale of Traditional Chinese Medicine scores at 6 weeks and 6 months after onset. All statistical analyses were performed according to the intention-to-treat principle. Results Among 252 randomized patients (198 men [78.6%]; mean [SD] age, 60.7 [7.5] years), 231 were included in the modified intention-to-treat analysis (115 in the MA group and 116 in the SA group). Compared with the SA group, the MA group had significant increases in AQ (difference, 7.99 points; 95% CI, 3.42-12.55 points; P = .001) and CFCP (difference, 23.51 points; 95% CI, 11.10-35.93 points; P < .001) scores at week 6 and showed significant improvements in AQ (difference, 10.34; 95% CI, 5.75-14.93; P < .001) and CFCP (difference, 27.43; 95% CI, 14.75-40.10; P < .001) scores at the end of follow-up. Conclusions and Relevance In this randomized clinical trial, patients with poststroke motor aphasia who received 6 weeks of MA compared with those who received SA demonstrated statistically significant improvements in language function, quality of life, and neurological impairment from week 6 of treatment to the end of follow-up at 6 months after onset. Trial Registration Chinese Clinical Trial Registry: ChiCTR1900026740